Ulcerative Colitis: Shifting Sands - Geert R. A. M. D'Haens; James O. Lindsay; Remo Panaccione; Stefan Schreiber (Adis, Springer Healthcare, 2019)
Abstract Ulcerative colitis (UC) is a chronic inflammatory bowel disease associated with considerable disease burden. We review some current misconceptions about UC in adults with the aim of optimizing care for patients. Although UC and Crohn's disease (CD) are considered discrete diseases, distinctions between them are not always clear-cut and phenotypes may change over time. Patient management should take into account disease manifestations, disease severity and extent, and response to prior treatments. Although disease extent often defines severity, distal UC is not always less disabling than extensive disease as patients can progress to more extensive disease. In addition, severe proctitis can give rise to severe and debilitating symptoms, with a substantial impact on health-related quality of life. UC carries an increased risk of colorectal cancer (CRC) compared with CD; however, more recent data indicate a similar risk of CRC in CD with colonic involvement as with UC. Corticosteroids are widely used to induce remission in UC, and prolonged use of steroids in patients with UC is common, but corticosteroid-free maintenance of remission is an important therapeutic goal. Although biologic therapies provide a valuable treatment option in UC, they are not clinically effective in all patients and are also associated with secondary loss of response.